Метод борьбы с перегрузкой на SIP-сервере с учетом динамического приоритета и текущей фазы установления соединения - Кузьминых, Е. Д. (Проблеми телекомунікацій, 2012)
A SIP-server overload control method that implement call control algorithm with dynamic priority and LIFO service discipline under overload using the current phase of the connection is proposed. This method increases the efficiency of SIP-networks under heavy load.
Keywords: SIP-сервер; контроль перегрузки; время установления соединения; пропускная способность; дисциплина обслуживания